Radiosensitization of human leukemic HL-60 cells by ATR kinase inhibitor (VE-821): phosphoproteomic analysis - Šalovská, Barbora; Fabrik, Ivo; Ďurišová, Kamila; Link, Marek; Vávrová, Jiřina; Řezáčová, Martina; Tichý, Aleš (International journal of molecular sciences, 2014)
DNA damaging agents such as ionizing radiation or chemotherapy are frequently used in oncology. DNA damage response (DDR)-triggered by radiation-induced double strand breaks-is orchestrated mainly by three Phosphatidylinositol 3-kinase-related kinases (PIKKs): Ataxia teleangiectasia mutated (ATM), DNA-dependent protein kinase (DNA-PK) and ATM and Rad3-related kinase (ATR). Their activation promotes cell-cycle arrest and facilitates DNA damage repair, resulting in radioresistance. Recently developed specific ATR inhibitor, VE-821 (3-amino-6-(4-(methylsulfonyl)phenyl)-N-phenylpyrazine-2-carboxamide), has been reported to have a significant radio- and chemo-sensitizing effect delimited to cancer cells (largely p53-deficient) without affecting normal cells. In this study, we employed SILAC-based quantitative phosphoproteomics to describe the mechanism of the radiosensitizing effect of VE-821 in human promyelocytic leukemic cells HL-60 (p53-negative). Hydrophilic interaction liquid chromatography (HILIC)-prefractionation with TiO2-enrichment and nano-liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis revealed 9834 phosphorylation sites. Proteins with differentially up-/down-regulated phosphorylation were mostly localized in the nucleus and were involved in cellular processes such as DDR, all phases of the cell cycle, and cell division. Moreover, sequence motif analysis revealed significant changes in the activities of kinases involved in these processes. Taken together, our data indicates that ATR kinase has multiple roles in response to DNA damage throughout the cell cycle and that its inhibitor VE-821 is a potent radiosensitizing agent for p53-negative HL-60 cells.
Keywords: proteom; Phosphorylation; Pyrazines; Humans; Gamma Rays; inhibitory proteinkinas; fosforylace; Sulfones; záření gama; lidé; ATM protein; Radiation-Sensitizing Agents; Protein Kinase Inhibitors; sulfony; radiosenzibilizující látky; Ataxia Telangiectasia Mutated Proteins; pyraziny; nádorové buněčné linie; Proteome; Cell Line, Tumor